Assessment and Evaluation in Chemistry Education - Andry Yana,; Dian Peniasiani, (Proceeding of International Joint Conference on UNESA, 2025)
This study aims to analyze the implementation of assessment and evaluation in chemistry learning at the secondary school level. The focus of the study includes the effectiveness of formative and summative assessments, improvement of laboratory skills, and students' higher-order thinking skills. The research method uses a descriptive quantitative approach with test instruments, observation sheets, and student engagement questionnaires. The results show a significant increase in post-test scores compared to pre-tests, with a normalized gain of 0.34 (moderate category). The findings also reveal that students' laboratory skills are higher than their higher-order thinking skills. Student engagement and the frequency of formative feedback have a positive effect on learning outcomes. This study emphasizes the importance of integrating formative assessment, laboratory evaluation, and instruments that encourage critical thinking in chemistry education.